Faktor Fundamental Terhadap Tingkat Underpricing Perusahaan Yang Melakukan Initial Public Offering (IPO) - Muhani Muhani; Nia Eka Pramelia; Molina Molina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
This study aims to find out the influence of debt to equity ratio, return on asset, return on equity and firm size on the level of underpricing in companies that conduct an Initial Public Offering (IPO) in Indonesia Stock Exchange period 2014-2019. The population in this study is all companies that conducted an Initial Public Offering (IPO) in Indonesia Stock Exchange period 2014-2019. Determination of the sample using a purposive sampling method through certain criteria in order to obtain a sample of 115 companies. The analysis method used in this study was multiple linear regression method. The results showed that: (1) debt to equity ratio has positive and insignificant effect on the level of underpricing; (2) return on asset has negative and significant effect on the level of underpricing; (3) return on equity has negative and insignificant effect on the level of underpricing; and (4) firm size has negative and significant effect on the level of underpricing.